ANALISIS PERBANDINGAN KUALITAS JARINGAN 4G LTE PADA PROVIDER TELKOMSEL, INDOSAT, XL, DAN SMARTFREN DI FAKULTAS TEKNIK UPN VETERAN JAKARTA MENGGUNAKAN METODE QUALITY OF SERVICE (QOS) - Rangga Wijaya (2023)
The internet has become a primary necessity for society, especially for students. Students naturally want to choose a mobile network operator that is adequate and optimal to meet their internet needs. This research aims to analyze and compare the network quality among providers using the Quality of Service (QoS) method. The providers being tested are Telkomsel, Indosat, XL, and Smartfren. The QoS parameters to be measured include Throughput, Delay, Jitter, and Packet Loss, using the WireShark and OpenSignal applications. The measurements were conducted in two locations, the FT UPNVJ Student Union Room and the vicinity of FT UPNVJ. The analysis of the Quality of Service (QoS) measurement results in the FT UPNVJ Student Union Room shows that Indosat is the most optimal and stable provider to be used in the FT UPNVJ Student Union Room, with the following QoS parameter values: Throughput (2837.6 Kbps), Delay (2.98), Jitter (2.98), and Packet Loss (0.1136%). On the other hand, in the vicinity of FT UPNVJ, XL is the most optimal and stable provider to be used, with the following QoS parameter values: Throughput (2768.8 Kbps), Delay (3.29 ms), Jitter (3.29 ms), and Packet Loss (0.3478%).